Effect of mindfulness-based cognitive therapy vs. psychoeducational intervention on plasma brain-derived neurotrophic factor and cognitive function in bipolar patients: a randomized controlled trial - Carracedo-Sanchidrian, Diego; de Dios-Perrino, Consuelo; Bayon-Perez, Carmen; Rodriguez-Vega, Beatriz; Bravo-Ortiz, Maria-Fe; Ortega, Miguel Á.; González-Pinto, Ana-Maria; Lahera, Guillermo (Frontiers in Psychiatry, 2024)
Introduction Few controlled trials have assessed the benefits of Mindfulness Based Cognitive Therapy (MBCT) on cognitive functions and brain-derived neurotrophic factor (BDNF) in bipolar disorder (BD). This study aims to evaluate the impact of MBCT adjunctive treatment on these variables. Main hypothesis was that MBCT would improve cognitive functioning and BDNF more than Psychoeducation and TAU. Methods Randomized, multicenter, prospective and single-blinded trial. Included BD outpatients randomly assigned to three treatment arms: MBCT plus treatment as usual (TAU), Psychoeducation plus Tau and TAU. Cognitive functions were assessed with Continuous Performance Test-III, Stroop Test, Trail Making Test, Digit Span and Letter-Number Sequencing from Wechsler Adult Intelligence Scale III, Face Emotion Identification Task and Face Emotion Discrimination Task. BDNF serum level was measured with ELISA. Patients were assessed at baseline, 8 weeks and 6 months. Results Eighty-four patients were recruited (TAU = 10, Psychoeducation = 34, MBCT = 40). No significant differences between treatment groups were found. MBCT does not achieve better results than Psychoeducation or TAU. Discussion Being Psychoeducation and TAU efficient interventions, as well as the scarce duration of a more complex intervention, such as MBCT, are suggested as explanatory variables of these results. Trial registration ClinicalTrials.gov: NCT02133170. Registered 04/30/2014.